Tegal Deso: Wujud Ungkapan Syukur Masyarakat Dusun Bongso Wetan, Menganti, Gresik - Nurul Izzah (Sunari Penjor : Jurnal of Anthropology, 2020)
Tegal Deso is a ceremony that aims as an expression of human gratitude for God who has provided sustenance and asks for safety in order to avoid calamities that can threaten the welfare of the local community. Tegal deso is held by the people of Bongso Wetan Hamlet once a year, which is a multicultural community, namely 376 families of Muslims and 223 of Hindus. Trust in dhanyang sing mbaurekso deso is a central point in organizing the Tegal Deso ceremony. For this reason, this research was conducted to determine how the implementation process and function of the Tegal Deso ceremony in order to integrate the people of Bongso Wetan Hamlet. This research approach uses descriptive qualitative. This research is expected to reveal facts that occur in the field from various existing events and phenomena.